2013
DOI: 10.2134/jeq2012.0500
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Adsorption onto Iron Oxide Layers beneath Coal-Mine Overburden Spoil

Abstract: A field experimental study to determine the feasibility of sequestering dissolved selenium (Se) leached from coal-mine waste rock used an iron (Fe)-oxide amendment obtained from a mine-drainage treatment wetland. Thirty lysimeters (4.9 × 7.3 m), each containing 57.7 t (1.2-1.8 m thickness) of mine-run carbonaceous shale overburden, were installed at the Hobet mine in southeastern West Virginia. The fine-grained Fe-oxide was determined to be primarily metal oxides (91.5% ferric and 4.37% aluminous), with minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The total Se mass release is consistent with the lack of measurable loss of Se from the piles based on Se D data, which, in turn, is consistent with the results of a fieldscale trial on coal waste rock in West Virginia conducted by Donovan and Ziemkiewicz. 28 They observed no depletion in Se over 2 years and acknowledged that the variability in Se concentrations in the waste rock could have made the depletion rate difficult to detect. In contrast to the above, samples from FRO differed from those from LCO and the Mist Mountain Formation (see Table S3 of the Supporting Information).…”
Section: ■ Results and Discusssionmentioning
confidence: 99%
“…The total Se mass release is consistent with the lack of measurable loss of Se from the piles based on Se D data, which, in turn, is consistent with the results of a fieldscale trial on coal waste rock in West Virginia conducted by Donovan and Ziemkiewicz. 28 They observed no depletion in Se over 2 years and acknowledged that the variability in Se concentrations in the waste rock could have made the depletion rate difficult to detect. In contrast to the above, samples from FRO differed from those from LCO and the Mist Mountain Formation (see Table S3 of the Supporting Information).…”
Section: ■ Results and Discusssionmentioning
confidence: 99%
“…This discrepancy was attributed to differences in leaching rate caused by differences in temperature, water throughput, and surface area. A similar field scale experiment in West Virginia over two years did not provide any evidence of depletion of Se from waste rock, though natural variability would have made a depletion rate difficult to detect over such a short time frame (Donovan and Ziemkiewicz, 2013). Several studies have found a strong relationship between sulfate and Se concentrations in surface coal mining watersheds (Palmer et al, 2010;Lindberg et al, 2011;Day et al, 2012;Kennedy et al, 2012), due to similar geochemical processes releasing both sulfate and Se (Diehl et al, 2012).…”
Section: How Does Mining Practice Affect Se Loading?mentioning
confidence: 92%
“…A combination of fine particles, high surface area and the affinity of iron oxides for Se and other trace elements makes ochres a natural trap for groundwater solutes. Ochre has even been deployed to extract Se from waters draining through coal waste (Donovan & Ziemkiewicz 2013). The situation at Mam Tor is very similar, where ochres are precipitated from, but also extracting Se from, the waters draining through the landslipped shale.…”
Section: Selenium Residencementioning
confidence: 99%